2022
DOI: 10.1002/cbf.3691
|View full text |Cite
|
Sign up to set email alerts
|

Rab34 plays a critical role as a bidirectional regulator of osteoclastogenesis

Abstract: Accumulating evidence suggests that Rab GTPases representing the largest branch of Ras superfamily have recently emerged as the core factors for the regulation of osteoclastogenesis through modulating vesicular transport amongst specific subcellular compartments. Among these, Rab34 GTPase has been identified to be important for the post-Golgi secretory pathway and for phagocytosis; nevertheless, its specific role in osteoclastogenesis has been completely obscure. Here, upon the in vitro model of osteoclast for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Additionally, Rab11b, but not Rab11a, was reported to be essential for the recycling of Tfn receptors to the cell surface 44 . Moreover, our previous studies revealed (1) the suppressive role of lysosomal Rab44 in regulating osteoclastogenesis by controlling the levels of intracellular calcium, thereby activating NFATc‐1, 31 and (2) the regulatory role of lysosomal Rab27A in modulating the multinucleation and lysosome‐related organelles in OCs, 45 and (3) a bidirectional function of Rab34 in regulating osteoclastogenesis by directing the vesicular transport of c‐fms and RANK surface receptors, as well as facilitating the secretion of lysosomal enzymes such as MMP9 and CTSK in OCs 46 . On the contrary, Rab11a and Rab11b were not localized to lysosomes in both OC precursors and OCs, 15,16 indicating that Rab11 regulates bone resorption predominantly by regulating OC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Rab11b, but not Rab11a, was reported to be essential for the recycling of Tfn receptors to the cell surface 44 . Moreover, our previous studies revealed (1) the suppressive role of lysosomal Rab44 in regulating osteoclastogenesis by controlling the levels of intracellular calcium, thereby activating NFATc‐1, 31 and (2) the regulatory role of lysosomal Rab27A in modulating the multinucleation and lysosome‐related organelles in OCs, 45 and (3) a bidirectional function of Rab34 in regulating osteoclastogenesis by directing the vesicular transport of c‐fms and RANK surface receptors, as well as facilitating the secretion of lysosomal enzymes such as MMP9 and CTSK in OCs 46 . On the contrary, Rab11a and Rab11b were not localized to lysosomes in both OC precursors and OCs, 15,16 indicating that Rab11 regulates bone resorption predominantly by regulating OC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…OC progenitors, derived from monocyte/macrophage lineage, are differentiated into mature, multinucleated OCs via a series of osteoclastogenic signaling pathways [3,4]. In principle, OC differentiation and maturation, also known as osteoclastogenesis, are primarily induced by the binding of two critical cytokines, including (1) the receptor of nuclear factor kappa-B ligand (RANKL) to its specific RANK receptor and (2) the macrophage colony-stimulating factor (M-CSF) to c-fms receptor in cell surface of OC progenitors [5,6]. RANKL/RANK signaling triggers the commitment of monocyte/ macrophage precursors to the OC lineage and subsequently mature, multinucleated OCs via predominantly activating six downstream signaling cascades comprising (1) the nuclear factor of activated T cells cytoplasmic-1 (NFATc-1); (2) nuclear factor kappa B (NF-κB); (3) phosphatidylinositol 3-kinase (PI3K/Akt); (4) Jun N-terminal kinase (JNK); (5) extracellular signal-regulated kinase (Erk); and (6) p38 mitogen-activated protein kinase (MAPK) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%